2016
DOI: 10.1128/jvi.00704-16
|View full text |Cite
|
Sign up to set email alerts
|

Rotavirus NSP1 Associates with Components of the Cullin RING Ligase Family of E3 Ubiquitin Ligases

Abstract: The rotavirus nonstructural protein NSP1 acts as an antagonist of the host antiviral response by inducing degradation of key proteins required to activate interferon (IFN) production. Protein degradation induced by NSP1 is dependent on the proteasome, and the presence of a RING domain near the N terminus has led to the hypothesis that NSP1 is an E3 ubiquitin ligase. To examine this hypothesis, pulldown assays were performed, followed by mass spectrometry to identify components of the host ubiquitination machin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
38
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 28 publications
(39 citation statements)
references
References 48 publications
(79 reference statements)
0
38
0
1
Order By: Relevance
“…In several in vitro models, rotavirus NSP1 inhibits the host IFN response by preventing IFN from being transcribed (35,51). Recent studies have shown that NSP1 acts as an adaptor that links the host Cullin-E3 ligase complex with β-transducin repeat-containing protein (β-TrCP), which is a necessary component for NF-κB-mediated induction of IFN transcripts (77,78). Through this interaction with the Cullin-E3 ligase complex, NSP1 facilitates the proteasomal degradation of itself and β-TrCP (78).…”
Section: Discussionmentioning
confidence: 99%
“…In several in vitro models, rotavirus NSP1 inhibits the host IFN response by preventing IFN from being transcribed (35,51). Recent studies have shown that NSP1 acts as an adaptor that links the host Cullin-E3 ligase complex with β-transducin repeat-containing protein (β-TrCP), which is a necessary component for NF-κB-mediated induction of IFN transcripts (77,78). Through this interaction with the Cullin-E3 ligase complex, NSP1 facilitates the proteasomal degradation of itself and β-TrCP (78).…”
Section: Discussionmentioning
confidence: 99%
“…Reciprocal coimmunoprecipitation studies subsequently showed RV‐NSP1 to associate with the PAZ domain containing span of AGO2 via its own N‐terminal domain independent of any RNA intermediates and residue phosphorylation, justifying degradation of AGO2 in presence of N‐terminal domain of RV‐NSP1 (Figure a–d, F; Figure S5A, C). This is in contrast to the fact that substrate binding specificity of RV‐NSP1 generally lies in its highly variable C‐terminal half (Lutz et al, ; Morelli et al, ). The association between AGO2 and RV‐NSP1 (Figure e, Figure S5B) as well as ubiquitin enrichment of AGO2 (Figure S3F) were also observed at early hour of RV‐SA11 infection.…”
Section: Discussionmentioning
confidence: 92%
“…This was also supported by similar restoration of AGO2 protein levels in RV‐NSP1‐transfected cells in response to 5 μM of reversible proteasome inhibitor MG‐132 but not to 1 μM of lysosomal inhibitor Bafilomycin A1 (Figure S3D). In addition to the putative E3 ubiquitin ligase activity intrinsic to RV‐NSP1, co‐opted host E3 ubiquitin ligase complex Cullin has recently been implicated to be interacting with (Ding et al, ; Lutz, Pace, & Arnold, ) and be involved in mediating proteasomal degradation of host substrates (Davis, Morelli, & Patton, ; Ding et al, ). Interestingly, inhibition of E3 ubiquitin ligase activity of Cullin by MLN4924 (500 nM) failed to rescue RV‐NSP1‐mediated reduction in AGO2 levels in MA104 cells (Figure d), suggesting AGO2 degradation by RV‐NSP1 to be independent of co‐opted Cullin machinery.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations